Le travail collectif, outil d'une école inclusive ? - Serge Thomazet; Corinne Mérini (Université de Provence, 2014)
Implementing inclusive education implies the development of a collective cross-professional space (intermétier) which would help linking the school with its. Based on a second analysis of two studies realized with experienced specialist teachers and novice mainstream teachers, we describe resistance to the collective practices, from the point of view of these professionals. These two studies have the same configuration of research-intervention process and a common methodology based on self and cross confrontation interviews, using videotaped professional situations. The results point to two types of obstacles. The first concerns work-related dilemmas whereas the second is due to the tensions caused by the cross-professional plurality.